Cassava seed systems in Southeast Asia: Structure, functioning, and implications - Delaquis, Erik Lucien (2023)
Seed systems have emerged as an important type of complex system which are common targets of interventions aiming to improve agricultural productivity, resilience, and societal outcomes. Along with these needs comes the realization that still today relatively little is known about the fundamental structure of many seed systems underpinning important agricultural crops. One such example is cassava (Manihot esculenta Crantz), which has become one of the most important global carbohydrate crops. With a developed industrial processing sector, the context of the sector’s seed system draws in stakeholders including farmers, specialized seed traders, starch and chip industry stakeholders, and government actors. Into this complex scenario, invasive pests and diseases add to the litany of biotic and abiotic pressures calling for increased varietal turnover. This thesis embraces the lack of available information on Southeast Asian cassava seed systems as an opportunity to investigate multiple interrelated aspects of the system, aiming both to chart an undocumented landscape and to provide insights into its functioning and potential for improvement. Taking the Greater Mekong Subregion as the geographic unit of investigation, this is accomplished through mapping of informal seed exchange networks, institutional analysis of formal early generation seed initiatives, review of the chronological and spatial changes in seed regulatory regimes, and experimental investigation of farmer willingness to pay for improved seed products. The resulting analysis paints a picture of a large, highly regionalized system, in which informal and formal actors both contribute to an impressive long-distance reach of seed driven by strong demand for improved seed from farmers and industry. Very different national models for producing and disseminating early generation seed contribute to a transboundary network that routinely operates in defiance of increasingly strict regulatory structures. I conclude by highlighting contributions of the findings to the overall study of seed systems and the development of conceptual frameworks embracing the complexity of seed systems in the real world and their implications for cassava seed systems in the Greater Mekong Subregion.